2016
DOI: 10.1111/cgf.12933
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Topology‐based Methods in Visualization

Abstract: This paper presents the state of the art in the area of topology-based visualization. It describes the process and results of an extensive annotation for generating a definition and terminology for the field. The terminology enabled a typology for topological models which is used to organize research results and the state of the art. Our report discusses relations among topological models and for each model describes research results for the computation, simplification, visualization, and application. The pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
94
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(94 citation statements)
references
References 229 publications
0
94
0
Order By: Relevance
“…Previous work has demonstrated that tracking graphs are ideally suited to visualize the evolution and relation of components over time [HLH*16]. Several methods have been proposed to identify and track components of time‐varying scalar fields.…”
Section: Related Workmentioning
confidence: 99%
“…Previous work has demonstrated that tracking graphs are ideally suited to visualize the evolution and relation of components over time [HLH*16]. Several methods have been proposed to identify and track components of time‐varying scalar fields.…”
Section: Related Workmentioning
confidence: 99%
“…There exists a huge body of work that demonstrates that tracking graphs are ideally suited to visualize the evolution and relation of components over time [9]. To utilize these methods we first compute a volumetric representation of the point clouds via an adaptation of Shepard's kernel method [13] for three-dimensional domains.…”
Section: Related Workmentioning
confidence: 99%
“…More information on the extraction and tracking of feature is compiled in [PVH*03]. More recent reports summarize the efforts in topology‐based [HLH*16, LHZP07] and specifically unsteady topology‐based [PPF*11] flow visualization.…”
Section: Introductionmentioning
confidence: 99%
“…We refer to Heine et al . [HLH*16], Scheuermann and Tricoche [ST05] and Weinkauf [Wei08] for a comprehensive introduction into topology‐based methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation